End of course work and its contribution to initial teacher training: an analysis focused on ISCED of Cabinda, Angola - Canhici, Maria Helena (2017)
The article analyses the option of using “End of Course Work” to finish the training teacher course in Cabinda Instituto Superior de Ciências da Educação (ISCED). Through interviews, the study analyses opinions of decision makers and heads of the Departments of Education and Research. In the opinion of these managers, the training model followed provides general knowledge concerning teaching and research contents. However, it doesn’t provide specific knowledge about teaching practices. The data also show that, although the curricular option of “End of Course Work”, and not an internship report, is not considered ideal for the training of future teachers, it allows students to develop research skills related with scientific domains of their studies, enabling better course performance.